2022
DOI: 10.3390/ijerph19074239
|View full text |Cite
|
Sign up to set email alerts
|

Did Children in Single-Parent Households Have a Higher Probability of Emotional Instability during the COVID-19 Pandemic? A Nationwide Cross-Sectional Study in Japan

Abstract: The influence of public health measures against COVID-19 in Japan on child mental health by household type is unknown. This study aimed to investigate whether COVID-19 and the declaration of a state of emergency in Japan affected children’s mental health between single-parent and two-parent households disproportionately. A large cross-sectional online survey was conducted from August to September 2020. The study included 3365 parents with children aged 0–14 years old who reported their children’s mental status… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…A recent study conducted in Japan during the COVID-19 pandemic asked parents with children aged 0–14 years to report their children’s daily activities. The study demonstrated that children from single-parent households spent more time engaging in activities such as watching online entertainment, and playing games compared to those from two-parent families (Naito et al, 2022 ). It was also found that preschool children whose mothers had an associate degree or below had a significantly higher mean value on the Constant Play subscale than preschool children whose mothers had a bachelor’s degree or higher.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study conducted in Japan during the COVID-19 pandemic asked parents with children aged 0–14 years to report their children’s daily activities. The study demonstrated that children from single-parent households spent more time engaging in activities such as watching online entertainment, and playing games compared to those from two-parent families (Naito et al, 2022 ). It was also found that preschool children whose mothers had an associate degree or below had a significantly higher mean value on the Constant Play subscale than preschool children whose mothers had a bachelor’s degree or higher.…”
Section: Discussionmentioning
confidence: 99%
“…Adolescents living in single-parent family, in foster care or with other relatives are more likely to engage in substance (mis)use in the two periods, before and at the end of the pandemic. Research finds higher emotional instability among children, living in singleparent households during the pandemic [40]. Higher economic vulnerability and emotional distress of single parents affects negatively young people's mental health, increasing the risk of engagement in substance (mis)use [41].…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, housing environments have been reported to affect mental health in many ways [32][33][34][35][36]. Especially following the lockdown triggered by the COVID-19 pandemic, research on housing environments and mental health has progressed in many fields [37][38][39][40]. However, researchers have been studying the importance of housing environments in mental health since before the pandemic.…”
Section: Housing Environment and Mental Healthmentioning
confidence: 99%